(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The study focused on determining the level of satisfaction and the factors involved in it, for employees of the Company Adara, SA Random survey of 400 employees from different areas of the company so applied. Results include the level of satisfaction of the employees of the company stands 89%, indicating that most of the employees have a high level of satisfaction working for the company. It was also possible to determine the factor considered the most important to employees when measuring satisfaction is enjoying his work, representing 46.25%. However, the company is recommended not to neglect this important aspect. DOI: http://dx.doi.org/10.5377/reice.v2i4.1723 REICE Vol. 2, No. 4, julio-diciembre 2014: 20-33